Natural pigment and natural mordant: Spectrophotometry studies / Nurul Idayu Abdullah - Abdullah, Nurul Idayu (Faculty of Applied Sciences, 2009)
The natural pigment was successfully extracted from Lawsonia inermis leaves and Allium Haemonatochiton skin in distilled water at 100 °C while the natural mordant was prepared of Terminalia Catappa and Oryza Sativa in distilled water. The crude extract of Allium Haemonatochiton gives a red maroon solution while the crude extract of Lawsonia inermis gives a reddish orange solution. The Terminalia Catappa crude extract produced a yellowish brown color while the Sativa Oryza crude extract produced a pale yellow color. In present study, the different mixture of natural pigment and natural mordant produced a difference shade of color. The maximum absorption for all samples was measured by UV-VIS Spectrophotometer. The maximum absorption spectra for mixture of Lawsonia inermis leaves with Oryza Sativa shows a hyperchromic effect while Lawsonia inermis with Terminalia Catappa and mixture of Allium Haemonatochiton with Oryza Sativa shows a hypsochromic shift but the mixture of Allium Haemonatochiton with Terminalia Catappa shows a bathochromic shift.